2003
DOI: 10.1038/sj.bjc.6600776
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of survivin in breast cancer

Abstract: Survivin is a member of the inhibitor of apoptosis (IAP) family, and is also involved in the regulation of cell division. Survivin is widely expressed in foetal tissues and in human cancers, but generally not in normal adult tissue. This study examined the expression of surviving protein in a series of 293 cases of invasive primary breast carcinoma. Survivin immunoreactivity was assessed using two different polyclonal antibodies, and evaluated semiquantitatively according to the percentage of cells demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
171
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(201 citation statements)
references
References 36 publications
23
171
6
Order By: Relevance
“…This implies, functionally, that the selective loss of expression of the nuclear form of Survivin may play a role in tumour progression or anaplasia. These data are consistent with that of recent publications of Survivin expression in breast and gastric carcinomas, which demonstrated that lower nuclear expression of Survivin was an independent prognostic indicator of poor prognosis (Okada et al, 2001;Kennedy et al, 2003). As the number of cases in our study was not large enough to assess the impact of nuclear Survivin staining as an independent prognostic factor in this subset of brain tumours, we cannot defend its use as a marker for clinical outcome at this time.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This implies, functionally, that the selective loss of expression of the nuclear form of Survivin may play a role in tumour progression or anaplasia. These data are consistent with that of recent publications of Survivin expression in breast and gastric carcinomas, which demonstrated that lower nuclear expression of Survivin was an independent prognostic indicator of poor prognosis (Okada et al, 2001;Kennedy et al, 2003). As the number of cases in our study was not large enough to assess the impact of nuclear Survivin staining as an independent prognostic factor in this subset of brain tumours, we cannot defend its use as a marker for clinical outcome at this time.…”
Section: Discussionsupporting
confidence: 90%
“…As discussed in detail in a recent publication of Survivin expression in breast carcinomas, as well as in several intracellular localisation studies of Survivin protein, multiple pools of Survivin exist within transformed cells and these likely have different functions (Fortugno et al, 2002;Mahotka et al, 2002b;Kennedy et al, 2003). Several different splice variants of Survivin also exist (Survivin, Survivin delta Ex 3, and Survivin-2B), as illustrated in Figure 5.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The numbers studied were similar with many being T2 and 61% node positive. Kennedy et al (2003) used the same antibody (AB469) as the present study but found a correlation between presence of Survivin and better prognosis. They evaluated nuclear and cytoplasmic reactivity separately and found nuclear staining to be associated with better outcome, whereas cytoplasmic staining was not significant.…”
Section: Discussionmentioning
confidence: 75%
“…Different prognostic significance of BIRC5 nuclear labeling in several tumor types has been reported in recent years, [45][46][47][48][49][50] as summarized in reference Li et al 51 For example, correlation of BIRC5 nuclear (but not cytoplasmic) staining with poor prognosis has been reported in ependymoma, esophageal squamous cell carcinoma, hepatocellular carcinoma, mantel cell lymphoma, and non-small cell lung cancer. [45][46][47][48] Paradoxically, BIRC5 nuclear staining was reported to be associated with better prognosis in gastric cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 99%